Intellectual capital disclosure and corporate governance structure among Malaysian Government Linked Companies (GLCs) / Musliha Musman - Musman, Musliha (2011)
This study examines the level of intellectual capital disclosure among the listed Malaysian GLCs by comparing them to the Non-GLCs for the period 2007-2009. In addition, this study also investigates the association between the intellectual capital disclosure and board structure among Malaysian GLCs. The board structure mechanisms comprise; board composition, role duality, board size and cross directorship. The control variables consist of the company-specific characteristics; leverage, profitability and age of the company. The content analysis is used to extract the intellectual capital disclosure items from the annual report. The result shows that the GLCs disclosed more intellectual capital information than Non-GLCs. Only the board size is positively significant associated to the intellectual capital disclosure of Malaysian GLCs. The result also shows that the leverage has significant association to the GLCs’ intellectual capital disclosure. The implication of this study is the GLCs’ board directors should need to monitor the company’s intellectual capital disclosure effectively even they have disclosed it higher than Non- GLCs. As GLCs with higher board member or low level of cross directorship are found to disclose more intellectual capital information, one way to increase such disclose is to increase the board size or keep a lower of cross directorship among GLCs.